Anais do 15o Colóquio Habermas e 6o Colóquio de Filosofia da Informação / - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2019)
The XV Habermas Colloquium was the ninth edition of the event organized by the group of research Philosophy and information policy at IBICT since 2010. From 2014 onwards simultaneously the Colloquium on the Philosophy of Information.
Keywords: Discurso; Ciências sociais aplicadas